A Bacillus subtilis strain with efficient algaecide of Microcystis aeruginosa and degradation of microcystins - Chen, Yuanyuan; Xiong, Fei; Zhu, Ying; Zhai, Dongdong; Liu, Hongyan; Zhang, Lin; Xia, Ming (Frontiers in Microbiology, 2024)
Global concerns over harmful cyanobacterial blooms brought on by eutrophication are now widespread. Aquatic ecological restoration techniques that use algicidal bacteria to control toxic algae show promise. A Bacillus subtilis S4 (S4) strain with strong Microcystis aeruginosa algicidal activity and the capacity to degrade microcystins (MCs) were successfully isolated and evaluated in this study. The dynamics of internal and extracellular MC concentration as well as the physiological response and morphological properties of M. aeruginosa were investigated in the M. aeruginosa/bacteria co-culture system. The findings demonstrated that when S4 density grew from 1 × 106 cells/ml to 1 × 108 cells/ml, the release of M. aeruginosa lysis and MCs was boosted; however, MCs dropped by approximately 90% within 18 h, regardless of bacterial density. Comparing the bacterial cell incubation system to the control and bacterial cell-free filtrate systems, the assessment of extracellular and intracellular MCs revealed a 95% reduction in MCs. The findings showed that 89% of MCs were decreased by bacterial cells, while 98% of M. aeruginosa cells were algaecided by bacterial metabolites. Sustainable eradication of M. aeruginosa and MCs has been accomplished by the combined efforts of the S4 strain and its metabolites. By secreting algicidal chemicals that are resistant to proteases, acid, base, and heat, the S4 strain indirectly acts as an algaecide. The S4 strain possesses a strong ability to break down MCs and a very effective and stable algaecide function, indicating that it can potentially treat eutrophic water with hazardous algae.